2018
DOI: 10.5847/wjem.j.1920-8642.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin dosing errors in the emergency department

Abstract: BACKGROUND:The study aimed to determine the frequency of enoxaparin dosing errors for patients who had a measured emergency department (ED) weight compared to those who did not have a measured ED weight, and to determine if demographic variables (e.g., weight, height, age, Englishspeaking, race) impact the likelihood of receiving an inappropriate dose.METHODS: This is a retrospective, electronic chart review of patients who received a dose of enoxaparin in the ED between January 1, 2008 and July 1, 2013. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In the first study, French-speaking patients treated by nonnative French-speaking health care providers were more likely to have their medication incorrectly reconstituted 25 . The second study showed that English-speaking patients in a hospital where the predominant language was English were more likely to experience a medication dosing error, 21 whereas the third did not find an association between patient language and medication errors among hospitalized patients in Israel 22 . Other studies examining the risk of harm among hospitalized, nonobstetric patients have not shown a difference in the risk of harm across linguistic groups 23,26 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first study, French-speaking patients treated by nonnative French-speaking health care providers were more likely to have their medication incorrectly reconstituted 25 . The second study showed that English-speaking patients in a hospital where the predominant language was English were more likely to experience a medication dosing error, 21 whereas the third did not find an association between patient language and medication errors among hospitalized patients in Israel 22 . Other studies examining the risk of harm among hospitalized, nonobstetric patients have not shown a difference in the risk of harm across linguistic groups 23,26 .…”
Section: Discussionmentioning
confidence: 99%
“…16,17 This large-scale population-based study included 311,131 hospitalizations, thus allowing us to obtain more precise and reliable estimates than previous studies. 16,[21][22][23]25,26 Studies conducted in the United States have shown that non-English-speaking women have a higher risk of obstetric trauma, 18,20 whereas pediatric patients from Spanish-speaking families have a higher risk of serious adverse events. 16,17 Three studies have also considered the impact of patient-provider language discordance on the rate of medication errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations